Comparison of Long-Term Survival Outcomes of T4a and T4b Colorectal Cancer - Lim, Ji Ha; Huh, Jung Wook; Lee, Woo Yong; Yun, Seong Hyeon; Kim, Hee Cheol; Cho, Yong Beom; Park, Yoon Ah; Shin, Jung Kyong (Frontiers in Oncology, 2022)
Background Although T4b is known to have worse oncologic outcomes, it is unclear whether it truly shows a worse prognosis. This study aims to compare the survival differences between T4a and T4b. Methods Patients who were pathologically diagnosed with T3 and T4 colorectal adenocarcinoma from 2010 to 2014 were included (T3, n = 1822; T4a, n = 424; T4b, n = 67). Overall survival (OS) and cancer-specific survival (CSS) were compared between T4a and T4b using the Kaplan-Meier method and log-rank test. Results In stage II, T4a had better OS and CSS than T4b (5-year OS, 89.5% vs. 72.6%; 5-year CSS, 94.4% vs. 81.7%, all p < 0.05), however, in stage III, there were no significant differences in survivals between groups (all p > 0.05). In multivariable analysis, T classification was not an independent risk factor for OS (p > 0.05). However, for CSS, when respectively compared to T3, T4b (HR 3.53, p < 0.001) showed a relatively higher hazard ratio than T4a (HR 2.27, p < 0.001). Conclusions T4a showed more favorable OS and CSS than T4b, especially in stage II. Our findings support the current AJCC guidelines, in which T4b is presented as a more advanced stage than T4a.